Effects of Erbium Family Laser on Shear Bond Strength of Composite to Dentin After Internal Bleaching - Kiomarsi, Nazanin; Arjmand, Yasaman; Kharrazi Fard, Mohammad Javad; Chiniforush, Nasim (Journal of Lasers in Medical Sciences, 2017)
Introduction: The aim of this study was to assess the effect of surface treatment with erbium: yttrium-aluminum-garnet (Er:YAG) and erbium, chromium: yttrium-scandium-gallium-garnet (Er,Cr:YSGG) lasers on shear bond strength of composite resin to recently bleached dentin. Methods: In this study, 40 extracted human premolars were selected. The teeth were cut 4 mm apical to the cusp tip and were randomly divided into four groups (n = 10 in each group) for shear bond strength testing. For bleaching, 35% hydrogen peroxide (H2o2) gel (Opalescence Endo, Ultradent, South Jordan, UT, USA) was applied to dentin surfaces of all specimens for 10 days. Before etching and bonding, in Er,Cr:YSGG and Er:YAG laser groups, dentin surfaces were irradiated with Er,Cr:YSGG and Er:YAG lasers, respectively. In Er,Cr:YSGG group, Er:YAG group and control group, composite restoration was performed immediately after bleaching while in common procedure group, composite restoration was performed after seven days. The teeth were then subjected to shear bond strength testing machine. The data were statistically analyzed using analysis of variance (ANOVA) and Tukey test. Results: The mean and standard deviation (SD) of shear bond strength was 4.3 ± 1.4 MPa for control group, 6.7 ± 2.0 Mpa for Er,Cr:YSGG group, 14.4 ± 3.7 Mpa for Er:YAG group and 19.4 ± 2.6 Mpa for common procedure group. Conclusion: The shear strength of composite to Er:YAG laser-treated bleached dentin was significantly higher than control group while significantly lower than common procedure.